مقارنة بين طرائق تقدير معالم الانحدار عند وجود مشكلة عدم تجانس التباين مع التطبيق العملي - علي, طه حسين; حسن, تارا احمد (Journal of Economics and Administrative Sciences, 2010)
In this research weights, which are used, are estimated using General Least Square Estimation to estimate simple linear regression parameters when the depended variable, which is used, consists of two classes attributes variable (for Heteroscedastic problem) depending on Sequential Bayesian Approach instead of the Classical approach used before, Bayes approach provides the mechanism of tackling observations one by one in a sequential way, i .e each new observation will add a new piece of information for estimating the parameter of probability estimation of certain phenomenon of Bernoulli trials who research the depended variable in simple regression  linear equation. in addition to the information deduced from the past experiences or self dependence. the research also contains a comparison between both approaches using practical application of both approaches for estimating the simple linear regression between the income and the state of having a house living in for the official in college of Administration and Economics in Salah-Alden University/Erbil .